Effect Of Composition Variation With Depth On Volatile Oil Reservoirs - Ego Syahrial (Testing Center for Oil and Gas LEMIGAS, 2010)
It has been known that the distribution of hydrocarbon components in a fluid column is affected of gravity. Many authors have shown the effect of composition variation within a hydrocarbon column due to gravity. In thick reservoirs as the depth increases, the mole fraction of the lighter hydrocarbon decreases, whereas the heavy fraction increases. These variations may affect reservoir fluid properties considerably. In studying reservoir processes, especially with miscible displacements, it is essential to have of underlying mechanisms. In this paper, we investigate the effect of composition variation with depth on volatile oil under depletion and miscible gas processes. A ternary diagram was used to identify the process displacement mechanisms at different locations. A new efficient compositional simulationapproach was used to model the volatile oil reservoir bahaviour. It was shown that the decreasing light component with depth caused different miscible displacement processes as the oil composition move toward limiting tie line in the ternary diagram. Saturation and reservoir pressures variation with depth were not linear in a thick reservoir. This non linearity increased with the increased in volatility of the oil. In the case of depletion, the concentration of light component decreased below its original composition in the produced layers. In vaporising-gas drive the light component gradually vaporized from the bottom to the top of reservoir, whereas the intermediate component decreased below its original composition from the bottom to the top of the reservoir